Antecedents and consequences of brand hate: Empirical evidence from the telecommunication industry - Olavo Pinto; Amélia Maria Pinto da Cunha Brand\~ao (European Journal of Management and Business Economics (EJM&BE), 2021)
Purpose - The purpose of this study is to place the antecedents and consequences of brand hate in the context of negative consumer-brand relationship in the telecommunication industry. It provides a response to the existing gap in the research on brand hate in consumer behavior in service brands. Design/methodology/approach - A survey-based data was modeled after theory that aims to apply concepts to the telecommunications industry. With a solid model grounded and context-adapted, a mediation analysis of the role of brand hate in negative antecedents and consequences toward brands was performed. Findings - Brand hate was found to mediate all the negative relationships proposed, while showing to be especially significant in mediating negative word of mouth. This model appropriately fits the services' marketing brand and revealed new insights into the function of brand hate in negative relationships that are specific to service marketing consumer brands. Research limitations/implications - Branding theory may benefit from deeper insights into the negative side of consumer-brand relationships. A broader illustration of its constituents in different industries and the recovery of the management approach to these circumstances bring innovation and a richer understanding, specially to the role of brand hate in the mediation context as seen in the literature (Hegner et al., 2017; Zarantonello et al., 2016) Practical implications - Managerial implications include assessing brands in analyzing and relating to different emotions and concepts from customers, allowing to prioritize and mapping the customer relationship touchpoints. Originality/value - The present study presents a first insight of brand hate in the context of the service industry of telecommunications in southern Europe while testing brand hate as a mediator involving negative predictors leading to negative outcomes in consumer-brand relationships.
Keywords: 650; Behavioral insight; Brand avoidance; Brand hate; Negative experience; Negative word of mouth; Relationship marketing